2016
DOI: 10.1177/0734904116659500
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the chemical and physical effects of halogenated fire suppressants addition on methane–air mixtures

Abstract: Previous experimental and numerical studies have demonstrated the unwanted promotion effect caused by potential halon replacements added to hydrocarbon–air mixtures. To explore this abnormal phenomenon, the chemical and physical contributions of the addition of C6F12O (Novec 1230) and C2HF5 (HFC-125) on the laminar flame speeds of the CH4–air mixtures are numerically investigated. Numerical simulations are conducted using the CHEMKIN-PRO software with newly developed fluorinated compounds’ mechanisms. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Considering the relationship between the physical and chemical effects of inhibitors investigated by Babushok et al , and Ren et al and the additivity principle for estimating the thermodynamic properties of chemicals, this methodology is mathematically expressed as normalΔ M = normalΦ ( R ) + ϕ ( P ) where Δ M represents the change of the combustion parameter and Φ( R ) and ϕ( P ) represent the chemical and physical effects, respectively. Based on eq , the definitions of the physical and chemical effects are as follows: When no inhibitor is added, the combustion parameter value of the fuel is defined as M 0 , and the physical and chemical effects of the inhibitor are both 0. When the inhibitor is added, the combustion parameter value of the fuel is defined as M 4 , and the physical and chemical effects of the inhibitor will be shown up simultaneously M 4 M 0 = normalΦ ( R ) + ϕ ( P ) When the inhibitor is set as an inert substance, the inhibitor only has physical effect, and the physical effect includes dilution and thermal effects M 2 M 0 = ϕ ( P ) = ϕ ( P D i ) + ϕ ( P T ) Compared with the inhibitor, the latent heat and specific heat capacity of helium (He) are very low and negligible.…”
Section: Quantitative Methodology Based On Fictitious Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the relationship between the physical and chemical effects of inhibitors investigated by Babushok et al , and Ren et al and the additivity principle for estimating the thermodynamic properties of chemicals, this methodology is mathematically expressed as normalΔ M = normalΦ ( R ) + ϕ ( P ) where Δ M represents the change of the combustion parameter and Φ( R ) and ϕ( P ) represent the chemical and physical effects, respectively. Based on eq , the definitions of the physical and chemical effects are as follows: When no inhibitor is added, the combustion parameter value of the fuel is defined as M 0 , and the physical and chemical effects of the inhibitor are both 0. When the inhibitor is added, the combustion parameter value of the fuel is defined as M 4 , and the physical and chemical effects of the inhibitor will be shown up simultaneously M 4 M 0 = normalΦ ( R ) + ϕ ( P ) When the inhibitor is set as an inert substance, the inhibitor only has physical effect, and the physical effect includes dilution and thermal effects M 2 M 0 = ϕ ( P ) = ϕ ( P D i ) + ϕ ( P T ) Compared with the inhibitor, the latent heat and specific heat capacity of helium (He) are very low and negligible.…”
Section: Quantitative Methodology Based On Fictitious Speciesmentioning
confidence: 99%
“…C 6 F 12 O (Novec 1230) is one of the most potential substitutes of Halon 1301, has both physical and chemical fire extinguishing effects, and has gradually gained the attention of the scientists . The physical and chemical effects of C 6 F 12 O addition on methane (CH 4 )/air flames have been researched by experimental and numerical methods by Pagliaro et al , Similarly, Xu et al and Ren et al also investigated the effects of C 6 F 12 O addition on CH 4 /air flames by using a counterflow configuration and a numerical method, respectively. Besides, the effect of C 6 F 12 O addition to a lithium-ion cell syngas flame was also investigated by Liu et al The behaviors of unwanted enhancement were observed for the above-mentioned research studies on premixed flames when the fraction of C 6 F 12 O addition is lower than the inerting concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the flame velocity decreased with the increase of addition amount. Previous studies have involved the analysis of the reasons for promoting flame combustion [9,[25][26][27][28], which is caused by the competitive relationship between the thermal effect of the inhibitor itself as a fuel combustion and the flame inhibition effect of the contained F element. And in the equivalence ratio of φ>0.67 showed inhibitory effect, chemical equivalent and more sensitive to the addition of inhibitors, in the case of φ=0.7, 1.0, 1.2, add C2HF5 X a =0.01, flame velocity reduced by 4.73%, 6.17%, 27.89%, this is because at this time inhibitor containing F inhibition is stronger than its thermal effect as fuel.…”
Section: Analysis Of Laminar Flame Velocitys Variationmentioning
confidence: 99%
“…The overall inhibition effectiveness of a suppressant consists of chemical effect and physical effect. The chemical and physical effect of a suppressant can be separated through artificially excluding chemical reactions containing the agent [18][19][20][21]. We introduced a virtual species, identified as "agent*" with the same thermodynamic and transport data as the agent.…”
Section: Chemical Saturation Effectivenessmentioning
confidence: 99%
“…Catalytic suppressants reduce concentrations of flame radicals through a regenerative cycle in which one molecule of suppressant recombines several flame radicals, whereas non-catalytic chemical suppressants reduce concentrations of flame radicals by scavenging and are generally less effective [22]. All chemical suppressants exhibit saturation effects [18,19,21] when the reduction of reactive radicals reaches an equilibrium concentration and the additional chemical agents only leads to a thermal effect [23]. CF 3 Br is a typical chemical suppressant with two chemical inhibiting moieties Br and CF 3 , of which Br moiety is a catalytic suppressant and CF 3 moiety is a non-catalytic suppressant.…”
Section: Chemical Saturation Effectivenessmentioning
confidence: 99%